THE DEVELOPING OF BUSY BOOK MEDIA FOR LEARNING PROCESS: IMPLEMENTING STUDY IN PRIMARY SCHOOL - Helminsyah, Helminsyah; Kasmini, Lili; Mardhatillah, Mardhatillah; Musdiani, Musdiani; Marlini, Cut; Subhananto, Aprian; Fuad, Zaki Al (Jurnal Ilmiah Teunuleh, 2022)
Interviews with SD Negeri 16 Banda Aceh class teachers revealed that the learning media used in grade I primary schools were less varied, less interesting, and the use of busy book media had never been used for students' speaking skills, with the development of busy book media expected to produce instructional media that were interesting and fun as well as being a solution for various problems in the learning process. Based on this case, the Busy Book media can be said to be valid used in the learning process ss in the first grade of elementary school. This has led researchers to conduct research under the title "Development of Busy Book Learning Media on Speaking Skills of Class I Students in SD Negeri 16 Banda Aceh. The formulation of the problem in this study y is: how to develop a valid Busy Book learning. media used for learning speaking skills of first grade students of SD Negeri 16 Banda Aceh? This study aims to produce a valid busy book learning media used for learning the speaking skills of grade 1 student at SD Negeri 16 Banda Aceh. This research is included in research and development (R&D). This study adapted the development procedure from Thiagarajan, a 4D (four-D) device development model. Data collection techniques used by researchers are questionnai re questionnaires for media experts, namely from the aspect of content, graphics and depth of the media. Research data were analyzed using quantitative and qualitative analysis techniques. The results of the study in the form of validator 1 assessment results get an avera ge value of 3.9 validity and the assessment category is "Valid used". validator 2 assessment results get an average value of 3.6 and the assessment category is "Valid used". and validator 3 obtained an average value of 4.03 and the assessment category was "Valid used. Thus, the Busy Book media can be said to be valid to be used for learning the speaking skills of grade 1 students at SD Negeri 16 Banda Aceh.